2023
DOI: 10.4070/kcj.2023.0117
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Physiology-Based Approaches for Plaque Vulnerability: Implications for Risk Prediction and Treatment Strategies

Abstract: Author's summary While coronary physiology and plaque vulnerability have been considered distinct attributes of coronary artery disease, evaluated from different diagnostic modalities, clinical data and underlying pathophysiology have demonstrated that there is a strong connection between hemodynamic properties and vulnerable plaque. This link suggests that using invasive physiological indexes to identify functional significance may also be somewhat useful in detecting plaque vulnerability. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“… 3) 6) With the advancement of technology, FFR can be noninvasively computed from CCTA and numerous studies have demonstrated a good correlation between invasive FFR and CCTA-derived FFR (CT-FFR) and its incremental information on practical decision-making. 7) 8) 9) 10) 11) 12) 13) 14) However, previous methods need the transfer of CCTA data to external facilities, supercomputing, and waiting times for processing. Several algorithms have been developed to mitigate these limitations and enable these processes on-site.…”
Section: Introductionmentioning
confidence: 99%
“… 3) 6) With the advancement of technology, FFR can be noninvasively computed from CCTA and numerous studies have demonstrated a good correlation between invasive FFR and CCTA-derived FFR (CT-FFR) and its incremental information on practical decision-making. 7) 8) 9) 10) 11) 12) 13) 14) However, previous methods need the transfer of CCTA data to external facilities, supercomputing, and waiting times for processing. Several algorithms have been developed to mitigate these limitations and enable these processes on-site.…”
Section: Introductionmentioning
confidence: 99%